2008
DOI: 10.1002/cjoc.200890224
|View full text |Cite
|
Sign up to set email alerts
|

From 1D Polymeric Chain to Two‐fold Parallel Interpenetration of (4,4) Net: Synthesis and Characterization of Two New Copper(II) Complexes Derived from Highly Polydentate Aminopolycarboxylate Ligand

Abstract: (2), [H 4 egta=3,12-bis(carboxymethyl)-6,9-dioxa-3,12-diazatetradecanedioic acid, bpe=1,2-bis(4-pyridyl)ethane, bipy=4,4'-bipyridyl] have been synthesized and structurally characterized by single-crystal X-ray diffraction, elemental analysis, IR spectra and TG analysis. The structure determination reveals that both 1 and 2 crystallize in a monoclinic system, space group P2 1 /c. Complex 1 exhibits a two-fold parallel interpenetration of (4,4) net framework consisting of 1D zigzag chains interlocked together t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Examples include complexes of yttrium(III) and most trivalent lanthanides (Ln = La-Lu), except for praseodymium and promethium (both radioactive with short half-lives), as well as lutetium (illustrated with a Gd example [13]), calcium, strontium, barium, cadmium, hafnium, and zirconium. (ii) Complexes where EGTA serves as a dinucleating bridge between two copper(II) [16][17][18][19] or two nickel(II) centers. (iii) Heterometallic combinations involving sophisticated clusters [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples include complexes of yttrium(III) and most trivalent lanthanides (Ln = La-Lu), except for praseodymium and promethium (both radioactive with short half-lives), as well as lutetium (illustrated with a Gd example [13]), calcium, strontium, barium, cadmium, hafnium, and zirconium. (ii) Complexes where EGTA serves as a dinucleating bridge between two copper(II) [16][17][18][19] or two nickel(II) centers. (iii) Heterometallic combinations involving sophisticated clusters [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Turning to the acid H 4 EGTA and its complexes with metal ions in the Cambridge Structural Database (CSD), it is observed that the crystalline structure of the acid itself is accessible [12]. Moreover, approximately 50 crystalline structures containing the tetravalent anion EGTA 4− or its partially protonated form HEGTA 3− as a ligand are also available [13][14][15][16][17][18][19][20][21][22]. A comprehensive analysis of these structures reveals three general compound types: (i) Complexes where EGTA primarily functions as a chelator for a metal center.…”
Section: Introductionmentioning
confidence: 99%